Analysis of Education Programs in New Zealand: Analisis Program Pendidikan di Selandia Baru - Saputra, Andra; Fitri, Nidya; Ananda, Azwar; Rusdinal, Rusdinal; Gistituati, Nurhizrah (Journal of Vocational Education and Information Technology (JVEIT), 2024)
This research analyzes educational programs in New Zealand through a comprehensive literature study, focusing on educational policies, curriculum structures, teaching methods, as well as challenges and solutions in overcoming educational gaps. The results show that education policy in New Zealand is very progressive and innovative, with initiatives such as "Digital Technologies & Hangarau Matihiko" integrating digital technologies into all aspects of education. The national curriculum, The New Zealand Curriculum (NZC), emphasizes the development of key competencies such as critical thinking and collaboration, and provides flexibility for schools to adapt learning programs to suit student needs. New Zealand teaching methods are very student-centred and based on active and collaborative learning, supported by the widespread use of technology. Despite this, challenges in overcoming educational disparities remain, especially regarding differences in academic achievement between students from various socio-economic and ethnic backgrounds. The New Zealand government has launched various programs to address these challenges, with positive results but requiring sustained effort. The conclusions of this research indicate that curriculum flexibility, student-centred teaching approaches, and technology integration are key factors supporting the success of the education system in New Zealand, providing valuable insights for improving education systems in other countries